Differential activation of ERK signaling in HPV-related oropharyngeal squamous cell carcinoma - Rong, Chao; Flechtenmacher, Christa; Dyckhoff, Gerhard; Bulut, Cem; Horn, Dominik; Plinkert, Peter K.; Heß, Jochen; Affolter, Annette (Cancers, 2019)
Human papillomavirus (HPV)-related oropharyngeal squamous cell carcinoma (OPSCC) forms a distinct tumor entity with better survival clinical outcome. Numerous underlying molecular mechanisms have been postulated for differences in treatment response, but the impact of MEK/ERK signaling, a main driver of carcinogenesis in various cancers including OPSCC and key player mediating therapy resistance remains elusive. In a retrospective experimental cohort study, primary tumor samples from OPSCC patients (n = 124) were available on tissue microarrays (TMAs) and expression levels of phosphorylated ERK1/2 (pERK1/2) were detected by immunohistochemical staining. Correlations of pERK1/2 expression patterns with clinicopathological features and clinical outcome were evaluated by statistical analysis. A low pERK1/2 expression was strongly associated with HPV-related OPSCC, while primary tumors with high pERK1/2 staining showed a distinctly worse survival outcome and were associated with higher cellular differentiation. Co-activation of both ERK1/2 and AKT was a common event and was associated with unfavorable prognosis in our cohort. However, the combinatorial analysis of pAKT (Ser473) and pERK1/2 did not strengthen the predictive power of pERK1/2, suggesting that pERK1/2 plays a more significant function in OPSCC. In summary, our data provide a compelling experimental and statistical evidence that low levels of tumor cell intrinsic ERK1/2 activation contribute at least in part to the favorable outcome of HPV-related OPSCC. On the other hand, presented findings indicate that non-HPV-related OPSCC with elevated ERK phosphorylation are at high risk for treatment failure and might benefit from targeted therapy of MEK/ERK signaling.